An AC Power Flow Analysis using Optimization Method for Grid-Connected AC Electrical Network - Vilaisarn, Youthanalack; Norher, Yaporlao; Chanthavong, Phanxay; Kiatoukaisy, Phetsila; Inthala, Soumek; Phrakonkham, Sengprasong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Alternative current power flow analysis (ACPF) is a key component for power system analysis, especially for planning the network infrastructure and analyzing its operation. Moreover, an ACPF is a base for learning an alternative current optimal power flow (ACOPF). According to these advantages, this article proposes the discussion on ACPF in detail in which can be used as a reference for helping the readers (e.g., students) deeply understand an ACPF and use in the particular works. This paper includes the basic theory for ACPF, formulation, and solution approach. Moreover, a nonlinear ACPF is formulated according to the optimization format and presented in this work. A MATLAB (i.e., fmincon) is used for solving the formulated problem. In order to validate the solution, the numerical results delivered by MATLAB are compared to those obtained by a commercial tool, POWERWORLD. Finally, the 5-bus and 8-bus balanced systems, which are close to the practical system, i.e., EDL transmission network structure, are deployed for validation.